MODEL PENGUATAN KEARIFAN LOKAL DALAM MENJAGA KEAUTENTIKAN WISATA KULINER LOMANG DI KABUPATEN KUANTAN SINGINGI - harto, syafri (Jurnal Niara, 2019)
The era of autonomy in the typical Kuantan Mudik culinary area does not develop like other regional foods, but the values ​​of local wisdom still exist. For this reason, this research seeks to multiply the model of strengthening local wisdom in maintaining the authenticity of lomang culinary tours in the regency of singing and singing. The results of the study explain the drivers of strengthening local wisdom are the ability to maintain, preserve, and pass on local wisdom. Pewarisan local wisdom value is intended so that the younger generation of Kuantan Singingi Regency can protect itself from the negative effects of modernization due to globalization, but it becomes an idea for expressing and appreciating local wisdom values ​​by empowering the community Kuantan Singingi District Government must include malomang activities as an event on the track runway event by utilizing a bottom-up system for millennials and communities that still maintain the Malomang tradition so that it becomes an attraction, with leverage like trees and crystallizes and fences like cages in lomang activities and marketing in tourist destinations.